Impact of Human Rights Education at School, Community and Individual Levels - Case Study of Georgia Research Essay - Gugeshashvili, Medea (Journal of Education in Black Sea Region, 2021)
Since its independence in 1991, the promotion of human rights has been a part of Georgia’s efforts towards the integration into Euro-Atlantic Institutions. However, difficulties in introducing the concept of individual, democratic and human rights are persistent in the teaching/learning process, as these concepts are still not organic and commonly understood in popular culture. Herewith, a growing level of political and societal polarisation between nationalistic and liberal forces impedes the process of effective promotion of universal human rights principles. The article analyzes the tensions between the core values of nationalism and liberal ideology in Georgia, as well as the supporting factors for the promotion of human rights education (HRE). It discusses the potential of HRE in mitigating the societal polarisation and reaching social cohesion around the basic civic values. A conclusion is made that, despite considerable progress achieved in promoting HRE in Georgia during the last decade, complexities remain related to the difficulty of introducing the concepts of individual, democratic and human rights in the teaching/learning process, as such concepts are still not organic and commonly understood in popular culture. Based on the best practices identified in various impact assessment studies on HRE worldwide, recommendations are offered for the schools to introduce transformative and emancipatory learning and make HRE effective through the application of the ‘wholeschool’ approach - an effective tool for bringing tangible changes to the school environment, as well as the impact on the household and community levels. Keywords: human rights education, social cohesion, Georgia, impact of education, wholeschool approach, social cohesion